Clinico-statistical study of temporomandibular joint ankylosis: Etiology and onset age - KINO, Koji; OHMURA, Yoshiaki; IZUMI, Yukou; WAKE, Hiroyuki; SHIBUYA, Tomoaki; AMAGASA, Teruo (Journal of the Japanese Society for the Temporomandibular Joint, 1994)
In our department, we performed 288 arthroplasties on 236 TMJ ankylosis patients from 1934 to 1987. We investigated the inpatient and outpatient chart, the operation record, and the X-ray film for each patient in order to determine the etiology, onset age, and interpositional materials, as well as the prognosis, complication, sequela and so on. In this paper, we report and discuss the etiology and the onset age. 1. The number of operations has decreased since 1963. The reasons for this decrease may be the development of chemotherapy which reduces inflammation and also the fact that TMJ trauma is now found early due to advances in imaging techniques. Another reason may be the increase in the number of hospitals undertaking TMJ arthroplasty. 2. Inflammation was the most common cause (119 patients; 50.4%), followed by trauma (73 patients; 30.9%). Ten cases were regarded as congenital (4.2%). Recently the rate of trauma has been the predominant cause. 3. Concerning local inflammation, osteomyelitis was the most common (35 patients; 43.2%), followed by otitis media (32 patients; 39.5%), and parotiditis (9 patients; 11.1%). 4. Polyarthritis was most common (12 patients; 31.6%), followed by febrile disease (7 patients; 22.5%), and pneumonia (6 patients; 18.4%) as for systemic inflammation. 5. As for the types of trauna, fall was the most common (40 patients; 54.8%), followed by traffic accidents (20 patients; 27.4%). Forceps delivery was found in 6 patients (8.2%). Also two cases occurred after TMJ discetomy. 6. The age range of TMJ ankylosis patients was from congenital to 65 years old. The number of patients whose onset age was from 0 to 5 years old was the biggest (129 patients; 54.7%), followed by 6-10 years old (58 patients; 24.6%). Among all the TMJ ankylosis patients, 187 patients (79.2%) were under 10 years of age when injured.